Predictors of Student Success in Canadian Polytechnics and CEGEPs - Ramey, Heather L.; Lawford, Heather L.; Chalmers, Heather; Lakman, Yana (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2018)
Student success in post-secondary education is an ongoing concern, however, research has focused on relatively homogeneous university samples. Moreover, Canadian research on predictors of student success is limited. Following recent trends, we examined non-cognitive, personal qualities, rather than cognitive predictors (e.g., IQ), of student success. Relying on a psychosocial model, we examined age, gender, perceived stress, maternal education, identity style, perseverance, and student engagement as predictors of student success in a multi-site sample of students attending a CEGEP in Quebec (N = 239; Mage = 18.6 years; 68.2% female) and a polytechnic school in Ontario (N = 209; Mage = 20.6 years; 71.3% female). Maternal education and perseverance emerged as significant predictors in both samples. Links between informational identity and cognitive engagement and student success differed by location. Our findings suggest the need to focus on student perseverance, and to consider identity and cognitive engagement dependent on the educational context.